Knowing Oldest Old’s Preferences May Improve their Healthcare: A Qualitative Study (Revista Iberoamericana de Bioética, 2020)
Oldest old people’s preferences are not taken into account though their importance in healthcare planning. To identify them, we undertook a qualitative study, using in-depth interviews, in a rural area of Toledo, Spain. The majority of participants rate the health care received as good. They favour building a trusting relationship with the physician, choosing to receive enough treatment to avoid the burden of suffering. They express the wish to die at home, but when an acute event occurs they want to be transferred to hospital. Knowing oldest old people health values will help to develop suitable healthcare systems.
Keywords: aged; 80 and over; clinical ethics